Acne Treatment Using a Combination Acupuncture and Fractional Laser - Mariani, Mariani; Ang, Suryawan (Rifa'Institute, 2023)
Introduction: Acne is a health problem that is often experienced, especially in adolescents and young adults. Acne can cause self-doubt and affect a person's quality of life. Objective: The purpose of this study is to explore the effectiveness of a combination of acupuncture and fractional laser therapy in treating acne problems. This study will collect data from respondents who have acne and see the results of their treatment using a combination of acupuncture and fractional laser therapy. Method: The research method used by the author is a quantitative experimental design with a pre-post-test design. Result and Discussion: The results of this study will assist in understanding the effectiveness of combined acupuncture and fractional laser therapy in the treatment of acne and provide recommendations for clinical practice. The results showed that the use of acupuncture and fractional laser combination therapy in acne cases showed significant changes. Conclusion: The GAGS score before therapy was at the severe level, changing to mild, and some were in the none category or completely cured, so that it can be concluded that this combination therapy can be an effective therapy for acne cases.